Growing Importance of Machine Learning in Compliance and Regulatory Reporting - Dey, Dhrubajyoti (European Journal of Multidisciplinary Studies, 2017)
Machine Learning is unquestionably one of the most exciting technology fields in the world today. The pace of discovery is almost unimaginably fast, and it seems each day we learn of new advancements, new technologies, new applications, and new opportunities. It’s inspiring, but also overwhelming. In this paper we will take a examine the role of Machine learning in Financial sector